PERBEDAAN PEMBERIAN ASI FIT DAN PIJAT OKSITOSIN TERHADAP LAMA PEMBERIAN ASI TRANSISI - Mulyadi, Jesica; Hanifa, Hanifa; Rachmawati, Rachmawati; Kurniawati, PS (Politeknik Kesehatan Kemenkes Bengkulu, 2020)
Abstract— ASI (Breast Milk) is a safe and suitable food for babies because it can prevent babies from the risk of gastrointestinal system disorders. Various methods used by postpartum mothers to increase milk production are Oxytocin Massage, IMD, Breast Care, frequency of breastfeeding (Bobak, 2005) and katuk leaf extract (ASI Fit) (Istiqomah and Setiawandari, 2017). The design of this study is quasi-experimental. The sample of this study was 30 respondents divided into 2 groups: 15 postpartum mothers given ASI Fit and 15 postpartum mothers given oxytocin massage. The research instrument used observation sheets. The analysis in this study used the Mann-Whitney test. The results showed the length of Transition ASI expenditure on postpartum mothers after being given Fit ASI and ASI massage for 1.87 days (1-3 days), the duration of Transition ASI expenditure on postpartum mothers after oxytocin massage which was 2.67 days (2-7 days) 4 days), there was a difference in the duration of expenditure for Fit ASI breastfeeding and oxytocin massage for postpartum mothers with p-value = 0.003 (p <0.05), transitional ASI expenditure in the Fit ASI group was faster than 0.800 days compared to the oxytocin group. Keywords — ASIFit, Oxytocin Massage, Transitional Breastmilk Expenditures